On the effective equations of a viscous incompressible fluid flow through a filter of finite thickness - Jäger, Willi; Mikelić, Andro (Communications on pure and applied mathematics, 1998)
We consider an incompressible and nonstationary fluid flow, governed by a given pressure drop, in a domain that contains a filter of finite thickness. The filter consists of a big number of tiny, axially symmetric tubes with nonconstant sections. We prove the global existence for the ε‐problem and find out the effective behavior of the velocity and the pressure fields.